Posttranslational modifications of proteins in diseased retina - Starr, Christopher R.; Gorbatyuk, Marina S. (Frontiers in Cellular Neuroscience, 2023)
Posttranslational modifications (PTMs) are known to constitute a key step in protein biosynthesis and in the regulation of protein functions. Recent breakthroughs in protein purification strategies and current proteome technologies make it possible to identify the proteomics of healthy and diseased retinas. Despite these advantages, the research field identifying sets of posttranslationally modified proteins (PTMomes) related to diseased retinas is significantly lagging, despite knowledge of the major retina PTMome being critical to drug development. In this review, we highlight current updates regarding the PTMomes in three retinal degenerative diseases—namely, diabetic retinopathy, glaucoma, and retinitis pigmentosa. A literature search reveals the necessity to expedite investigations into essential PTMomes in the diseased retina and validate their physiological roles. This knowledge would accelerate the development of treatments for retinal degenerative disorders and the prevention of blindness in affected populations.